Developing digital marketing strategies on educational program: a case study on BRAC Kumon Bangladesh - Rudra, Farhan Ishraq (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.